Preparation method and application of novel ionized water gel-based moisture power generation material

By using nanocarbon black and hygroscopic sea salt in moisture power generation materials, and designing serrated interfaces and patch metal electrodes, the problem of insufficient conductivity of traditional hydrogels is solved, and the electrical output performance and stability of moisture power generation materials are improved.

CN119834651APending Publication Date: 2025-04-15DALIAN UNIV OF TECH
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411879462.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Traditional hydrogels have poor conductivity in the field of moisture power generation, which limits current output and affects power generation performance. At the same time, the addition of conductive fillers will affect mechanical properties and water absorption capacity.

Method used

Nanocarbon black is used as a conductive filler and hygroscopic sea salt is introduced to design a serrated wet and dry interface, and combined with the structure of the patch metal electrode, a new ionic hydrogel-based moisture-powered power generation material is constructed.

Benefits of technology

It improves the electrical output performance and power generation power of moisture power generation materials, ensures the stability of the electrodes in the long-term power generation process, and reduces production and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119834651A_ABST
    Figure CN119834651A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a novel ionized water gel-based moisture power generation material. The material is composed of a carbon coating fabric, ionized water gel and a patch metal electrode. Wherein the nano carbon black is used as a conductive filler of the hydrogel and can enhance electric energy output by promoting functional group dissociation and ion migration. The high-hygroscopicity sea salt in the hydrogel can enhance the capture and transmission capability of the material on water molecules in the atmosphere, and ensures the continuous power output capability of the moisture power generation material. Due to the design of the zigzag dry-wet interface, the wettability between the hydrogel and the carbon black coating can be improved, the moisture absorption rate is increased, the contact area is increased, and therefore the power generation power is improved. The metal patch electrode can ensure the stability of long-term power generation of the material, and can be customized to reduce the contact resistance. A moisture power generation device prepared from the material can be used as a passive energy supply device and is suitable for the fields of self-powered sensors, wearable electronic equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wet gas power generation, and relates to a preparation method and application of a novel ion hydrogel-based wet gas power generation material. Background Art

[0002] With the continuous growth of global energy demand and the increasing depletion of traditional fossil energy, the exploration and development of new renewable energy has become an important issue in today's world. As an emerging energy conversion technology, wet gas power generation can effectively utilize the adsorption interaction between hygroscopic materials and water molecules in the atmosphere to convert the chemical potential energy in wet gas into electrical energy. The wet gas generator (MEG) is a key equipment in this technology. Wet gas power generation is pollution-free, sustainable and environmentally friendly. Therefore, the research and development of wet gas power generation materials is of great significance to achieve sustainable utilization of energy and environmental protection.

[0003] Hydrogel is a polymer material with high water absorption and high flexibility, and has great application potential in the field of wet gas power generation technology. However, the conductivity of traditional hydrogels is poor. This characteristic will limit the current output during wet gas power generation and affect the overall power generation performance. Although the conductivity of hydrogels can be improved by introducing conductive fillers, the addition of most conductive fillers will affect the mechanical properties and water absorption capacity of hydrogels. Therefore, screening and adding suitable conductive fillers has become a key issue. The shape of the hydrogel coating and its geometric interface design also have a great influence on the output voltage and power generation efficiency of wet gas power generation. Therefore, designing a suitable geometric interface and improving the coating process of the hydrogel is also a key point. In addition, traditional wet gas power generation materials collect charges by applying metal electrodes at both ends. The electrodes formed by the application may shift due to material deformation or external influences. In addition, the shape and size of the application are not easy to control accurately, which will also affect the contact resistance and power generation efficiency.

[0004] Therefore, in response to these performance bottlenecks of hydrogels in the field of wet gas power generation, the present invention proposes a preparation method and application of a novel ionic hydrogel-based wet gas power generation material. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention proposes a preparation method and application of a novel ionic hydrogel-based moisture power generation material to solve some of the above-mentioned performance defects.

[0006] The technical solution of the present invention is as follows:

[0007] A new type of ion hydrogel-based wet gas power generation material, which is composed of ion hydrogel, carbon-coated fabric and patch metal electrodes. In this structure, the ion hydrogel uses nano carbon black as a conductive filler, and introduces hygroscopic sea salt to enhance the electrical output performance of the wet gas power generation material. By designing the dry and wet contact interface between the ion hydrogel and the carbon-coated fabric to be a serrated shape, the moisture absorption rate of the material can be accelerated, thereby increasing the power generation power of the material. In addition, the patch metal electrode is firmly attached to the surface of the wet gas power generation material to ensure the stability of the electrode and the material during long-term power generation. Finally, a wet gas power generation material structure with a patch metal electrode-hygroscopic end of the ion hydrogel-based wet gas power generation material-dry end of the ion hydrogel-based wet gas power generation material-patch metal electrode as the basic unit is constructed.

[0008] A method for preparing a novel ionic hydrogel-based moisture power generation material, the steps are as follows:

[0009] In the first step, carbon-coated fabrics were prepared.

[0010] The second step is to prepare the ionic hydrogel.

[0011] In the third step, the ionic hydrogel is evenly coated on one side of the carbon-coated fabric to construct the hygroscopic end of the ionic hydrogel-based moisture power generation material. The other side of the carbon-coated fabric is not treated and serves as the drying end of the ionic hydrogel-based moisture power generation material. It is then placed in a constant temperature box for a period of drying.

[0012] In the fourth step, a pressure-assisted method is used to tightly fit the metal electrode to the hygroscopic end and the dry end of the ion hydrogel-based moisture power generation material in the form of a patch, and finally the moisture power generation material is successfully prepared.

[0013] Furthermore, the specific process of preparing the carbon-coated fabric in the first step includes: first, cutting the textile into a suitable size to obtain the textile to be loaded. Then, mixing the nano superconductive carbon black and sodium dodecylbenzene sulfonate in a certain mass ratio, and uniformly dispersing the above mixture in deionized water by ultrasonic dispersion to obtain a carbon black suspension. Then, the obtained carbon black suspension is uniformly coated on the surface of the textile. After the coating is completed, the textile is appropriately dried and heat-treated to fix the nano carbon black particles and optimize the conductivity of the carbon-coated fabric.

[0014] The carbon black suspension is evenly coated on the entire surface of the textile, in which the nano carbon black acts as a conductive filler for the hydrogel. The stacking of the filler particles forms a nano-micrometer-scale pore structure, which provides abundant channels for the flow of nanofluids. These channels are conducive to the water-induced dissociation of hydrophilic functional groups on the surface of the material, resulting in a water content gradient on both sides of the material, generating an ion concentration difference, driving ion migration, and thus improving the overall power output efficiency of the wet gas power generation material.

[0015] Furthermore, the specific process of preparing the ionic hydrogel in the second step includes: taking a certain mass of hygroscopic sea salt and dissolving it in deionized water to obtain a salt solution. Then, pouring polyvinyl alcohol (PVA) powder into the deionized water and rapidly stirring it for a certain period of time to obtain a PVA solution. Then, slowly pouring the salt solution into the PVA solution and rapidly stirring it, and standing it for a period of time to obtain an ionic hydrogel.

[0016] The ionic hydrogel coated on one side of the moisture power generation material introduces a variety of highly hygroscopic sea salts, which can enhance the material's ability to capture water molecules in the atmosphere, provide guarantees for the efficient adsorption and transmission of moisture, and also help improve the material's continuous electrical output performance.

[0017] Furthermore, in the third step, the ionic hydrogel is evenly coated on one side of the carbon-coated fabric. During the coating process, the dry-wet contact interface is designed to be serrated to create as many dry-wet contact interfaces as possible as the hygroscopic end of the ionic hydrogel-based moisture power generation material. In contrast, the other side of the carbon-coated fabric that is not coated with the ionic hydrogel serves as the dry end of the ionic hydrogel-based moisture power generation material. The obtained material is then placed in a constant temperature box for a predetermined period of drying to ensure the stability of the material structure and the consistency of performance.

[0018] The dry-wet contact interface is designed to be serrated to increase the contact area between the ionic hydrogel and the carbon black coating, which helps to improve the material's power generation. The serrated design can improve the wettability between the hydrogel and the carbon black coating. During the hydrogel's moisture absorption process, the serrated interface can more effectively guide the movement of water molecules, thereby accelerating the moisture absorption rate.

[0019] Furthermore, in the fourth step, a pressure-assisted method is used to closely fit the metal electrode to the hygroscopic end and the dry end of the ion hydrogel-based moisture power generation material in the form of a patch, and finally the moisture power generation material is successfully prepared.

[0020] The patch metal electrode will be firmly fixed on the material and will not easily move, which will help to generate electricity stably in the long term. In addition, the shape and size of the electrode can be customized as needed to accurately control the contact area between the electrode and the power generation material. The flat electrode is in close contact with the material surface, which can also reduce the contact resistance and improve the power generation efficiency of the material.

[0021] Furthermore, the novel ionic hydrogel-based moisture power generation material can spontaneously absorb moisture in the environment for power generation, can effectively start working when the relative humidity of the environment exceeds 30%, and can maintain an open circuit voltage of 0.65V and a current of 3.2×10 -2 mA cm -2 The short circuit current density capability.

[0022] Furthermore, the novel ionic hydrogel-based moisture power generation material can be used to construct a moisture power generation device by combining series and parallel connections to amplify its output voltage and output power. The device can spontaneously absorb moisture in the environment and convert the chemical potential energy in the moisture into electrical energy, so a moisture power generation device suitable for a variety of scenarios can be prepared. The device has the ability to spontaneously absorb ambient moisture and can effectively convert the chemical potential energy in the moisture into electrical energy.

[0023] Furthermore, the wet gas power generation device provided by the present invention can be used as a passive energy supply device, suitable for self-powered sensors, wearable electronic devices and other fields.

[0024] Furthermore, the patch metal electrode is gold, silver, copper, platinum or aluminum.

[0025] The principle of the present invention is that during the process of moisture power generation material absorbing water molecules, the hydrophilic functional groups on the surface of the material will dissociate, releasing charged free ions into the water. These ions act as charge carriers and can move freely in the solution. The hygroscopic properties of the side of the carbon layer fabric coated with ionic hydrogel are stronger than those of the uncoated side. After the moisture power generation material absorbs moisture, a water content gradient will form on both sides of the material, resulting in an ion concentration difference, which in turn drives ion migration. In this process, the freely moving ions spontaneously diffuse from the high concentration area to the low concentration area, generating a potential difference and an ion current, and ultimately outputting stable DC power to the outside.

[0026] Compared with the prior art, the advantages and positive effects of the present invention are as follows:

[0027] 1. The present invention proposes a method for preparing a novel hydrogel-based wet gas power generation material. Using nano carbon black as a conductive filler for the hydrogel can promote the dissociation of hydrophilic functional groups and induce ion migration, thereby improving the power output efficiency of the wet gas power generation material. The highly hygroscopic sea salt in the hydrogel can enhance the material's ability to capture water molecules in the atmosphere, ensure moisture adsorption and transmission, and thus improve the continuous power output capacity of the wet gas power generation material. The design of the serrated dry-wet interface can improve the wettability between the hydrogel and the carbon black coating, accelerate the moisture absorption rate, and increase the contact area between the ionic hydrogel and the carbon black coating, thereby increasing the power generation. The present invention uses a metal patch as the electrode of the ionic hydrogel-based wet gas power generation material, so that the metal electrode will be firmly attached to the surface of the material, which can ensure the stability of the electrode during long-term power generation. In addition, the shape and size of the electrode can be customized as needed, and the flat electrode is in close contact with the material surface, which can also reduce the contact resistance and improve the power generation efficiency of the material.

[0028] 2. Moisture is a resource that circulates continuously in nature, so moisture power generation is a sustainable way to obtain energy. The new hydrogel-based moisture power generation material proposed in the present invention does not need to burn any fuel during the power generation process, does not produce harmful emissions, does not pollute the environment, and is in line with the development direction of green energy. In addition, the moisture power generation material has a simple structure and low maintenance requirements, so the production cost and maintenance cost are also low. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a flow chart of the preparation method of the novel ionic hydrogel-based moisture power generation material of the present invention;

[0030] Figure 2 It is a schematic diagram of the side structure of the novel ionic hydrogel-based moisture power generation unit of the present invention;

[0031] Figure 3 It is a schematic cross-sectional structure diagram of the novel ionic hydrogel-based wet gas power generation unit of the present invention;

[0032] FIG4( a ) is a physical picture of an ionic hydrogel-based moisture power generation material;

[0033] Figure 4 (b) SEM image of the moisture absorption layer of the moisture power generation material at 100 um;

[0034] FIG4( c ) is a SEM image of the moisture absorption layer of the moisture power generation material at 10 μm;

[0035] FIG4( d ) is a SEM image of a dry layer of a carbon coating material not coated with ionic hydrogel at 100 μm;

[0036] FIG4( e ) is a SEM image of a dry layer of a carbon coating material not coated with an ionic hydrogel at 10 μm;

[0037] Figure 5 It is the open circuit voltage and short circuit current generated by the novel ionic hydrogel-based moisture power generation unit of the present invention under the condition of relative humidity of 80%;

[0038] Figure 6 It is the voltage and current generated by the novel ionic hydrogel-based moisture power generation unit of the present invention under different humidity conditions;

[0039] Figure 7 It is the test result of series voltage regulation of the novel ionic hydrogel-based wet gas power generation unit of the present invention;

[0040] Figure 8 It is the parallel current control test result of the novel ionic hydrogel-based wet gas power generation unit of the present invention;

[0041] Fig. 9 It is a schematic diagram of the series integration of the novel ionic hydrogel-based moisture power generation unit of the present invention;

[0042] Fig.10 It is a circuit schematic diagram of a passive energy supply device made by integrating the novel ionic hydrogel-based moisture power generation material of the present invention.

[0043] In the figure: 1 is a patch metal electrode, 2 is an ion hydrogel, 3 is a carbon-coated fabric, 4 is an ion hydrogel-based wet gas power generation unit, 5 is an integrated wet gas power generation device, 6 is a capacitor, and 7 is a load. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be described in detail and comprehensively below in conjunction with the accompanying drawings of the embodiments of the present invention. It should be noted that the described embodiments are only examples of a part of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.

[0045] like Figure 1 As shown, the present invention proposes a method for preparing a novel ionic hydrogel-based moisture power generation material, comprising the following steps:

[0046] Step 1, preparing carbon-coated fabric.

[0047] Step 2, preparing ionic hydrogel.

[0048] Step 3, the ionic hydrogel is evenly coated on one side of the carbon-coated fabric to construct the hygroscopic end of the ionic hydrogel-based moisture power generation material. The other side of the carbon-coated fabric is not treated and serves as the drying end of the ionic hydrogel-based moisture power generation material. It is then placed in a constant temperature box for a period of drying.

[0049] Step 4, using pressure-assisted means, the metal electrode is tightly fitted to the hygroscopic end and the dry end of the ion hydrogel-based moisture power generation material in the form of a patch, and finally the moisture power generation material is successfully prepared.

[0050] The specific process of preparing the carbon-coated fabric in step 1 includes: first, cutting the textile into a suitable size to obtain the textile to be loaded. Then, nano superconductive carbon black and sodium dodecylbenzene sulfonate are mixed in a certain mass ratio, and the above mixture is evenly dispersed in deionized water by ultrasonic dispersion to obtain a carbon black suspension. Then, the obtained carbon black suspension is evenly coated on the surface of the textile. After the coating is completed, the textile is properly dried and heat-treated to fix the nano carbon black particles and optimize the conductivity of the carbon-coated fabric.

[0051] The preparation of the ionic hydrogel in step 2 specifically includes: taking a certain mass of hygroscopic sea salt and dissolving it in deionized water to obtain a salt solution. Then, pouring polyvinyl alcohol (PVA) powder into the deionized water and rapidly stirring it for a certain period of time to obtain a PVA solution. Then, slowly pouring the salt solution into the PVA solution and rapidly stirring it, and standing it for a period of time to obtain the ionic hydrogel.

[0052] In step 3, the ionic hydrogel is evenly coated on one side of the carbon-coated fabric, serving as the moisture-absorbing end of the ionic hydrogel-based moisture power generation material. The other side of the carbon-coated fabric is not treated, serving as the drying end of the ionic hydrogel-based moisture power generation material. The material is then placed in a constant temperature box for a period of drying.

[0053] The patch metal electrode described in step 4 is tightly fitted with the hygroscopic end and the dry end of the ion hydrogel-based moisture power generation material, respectively, and the moisture power generation material is finally successfully prepared.

[0054] The technical solution of the present invention is further illustrated by the following embodiments.

[0055] Example 1

[0056] This embodiment is manufactured according to the above process for preparing ionic hydrogel-based moisture power generation materials, except that in step 3, when the ionic hydrogel is coated on the carbon-coated fabric, the dry-wet interface in the middle is designed to be serrated.

[0057] In this embodiment, an ionic hydrogel-based moisture power generation material is prepared. In a natural environment with a temperature of 20±5°C and a relative humidity of 80%±5%, the moisture power generation material can stably generate an open circuit voltage of 0.65V and a voltage of 3.2×10 -2 mA·cm -2 The short circuit current density output.

[0058] Comparative Example 1

[0059] The preparation process of this comparative example is the same as the process of preparing the ionic hydrogel-based moisture power generation material in the above embodiment, except that in step 3, when the ionic hydrogel is coated on the carbon-coated fabric, the middle dry-wet interface is designed to be a flat straight line incision.

[0060] In this comparative example, an ionic hydrogel-based moisture power generation material is prepared. In a natural environment with a temperature of 20±5°C and a relative humidity of 80%±5%, the moisture power generation material can stably generate an open circuit voltage of 0.60V and a relative humidity of 2.6×10 -2 mA cm -2 The short circuit current density output.

[0061] It can be found that the power generation performance of Comparative Example 1 is significantly lower than that of Example 1. This is because the serrated design can provide a larger contact area at the same length compared to the straight line design. This can increase the interaction points between the hydrogel and the carbon black coating, thereby improving the generation and collection efficiency of charges. The serrated interface may cause the electric field distribution to be more uneven, which is conducive to charge separation, that is, electrons and ions are more easily separated at the contact interface, thereby improving the power generation efficiency. In addition, the serrated interface can also enhance the capillary action, promote the movement of water inside the hydrogel along the interface, and help maintain the continuous wet state of the hydrogel, thereby ensuring the continuity of the power generation process.

[0062] Comparative Example 2

[0063] The preparation process of this comparative example is the same as the process of preparing the ionic hydrogel-based moisture power generation material in the above embodiment, except that in step 4, the electrode of the moisture power generation material is not made by means of a metal patch, but instead a liquid metal coating technology is used to evenly coat it on the moisture absorption end and the drying end of the ionic hydrogel-based moisture power generation material.

[0064] The ionic hydrogel-based moisture power generation device prepared in this comparative example can stably generate an open circuit voltage of 0.62V and a relative humidity of 2.8×10 - 2 mA cm -2 The short circuit current density output.

[0065] It can be found that the power generation performance of Comparative Example 2 is significantly lower than that of Example 1. This is because the metal patch method is better than the liquid metal coating method for making electrodes of wet gas power generation materials. Specifically, the metal patch method has the advantages of stable structure, controllable contact area and smaller contact resistance. The bonded metal electrode is fixed on the material and is not easy to move, which is conducive to long-term stable power generation. In addition, the shape and size of the electrode can be designed as needed to control the contact area with the power generation material. The flat electrode is in close contact with the surface of the material, which can also effectively reduce the contact resistance and improve the power generation efficiency.

[0066] like Figure 2 Side structure and structure of ionic hydrogel-based wet gas power generation unit Figure 3 As shown in the cross-sectional structure of , the present invention proposes a new type of ion hydrogel-based moisture power generation material, which is composed of a patch metal electrode 1, an ion hydrogel 2 and a carbon-coated fabric 3. In this structure, the ion hydrogel 2 is evenly coated on one side of the carbon-coated fabric 3 to form the moisture absorption end of the moisture power generation material. The other side of the carbon-coated fabric 3 is not treated and serves as the dry end of the moisture power generation material. The patch metal electrode 1 is tightly fitted with the moisture absorption end and the dry end of the ion hydrogel-based moisture power generation material, respectively, so as to construct a moisture power generation material structure with a patch metal electrode-the moisture absorption end of the ion hydrogel-based moisture power generation material-the dry end of the ion hydrogel-based moisture power generation material-the patch metal electrode as the basic unit.

[0067] As shown in Figure 4, (a) in the figure is a physical picture of the ion hydrogel-based moisture power generation material, and its structure includes a patch metal electrode layer, a hygroscopic layer of the ion hydrogel-based moisture power generation material, a dry layer of the carbon coating material not coated with ion hydrogel, and a patch metal electrode layer from top to bottom; (b) and (c) are SEM images of the hygroscopic layer of the moisture power generation material at different magnifications; (d) and (e) are SEM images of the dry layer of the carbon coating material not coated with ion hydrogel at different magnifications.

[0068] like Figure 5 As shown, the ionic hydrogel-based moisture power generation material unit proposed in the present invention exhibits stable electrical properties under a test environment with a relative humidity of 80%, and can continuously output an open circuit voltage of 0.65V and a short circuit current of 324μA for a long time.

[0069] like Figure 6 As shown, the ionic hydrogel-based moisture power generation material unit proposed by the present invention exhibits electrical output characteristics that vary significantly with relative humidity. The moisture power generation material unit can be started when the ambient relative humidity exceeds 30%. When the relative humidity reaches about 80%, the electrical output performance reaches a peak. Accordingly, the moisture power generation material unit can show high applicability and reliability in most practical application scenarios.

[0070] like Figure 7 and Figure 8 As shown, the ionic hydrogel-based wet gas power generation material units can be integrated in series and parallel. The integrated wet gas power generation device was placed in a closed experimental device with adjustable relative humidity. When the relative humidity in the device was set to 80%, it was observed that the output voltage of different numbers of wet gas power generation integrated devices showed a linear change trend. Similarly, the output current of different integrated devices also showed a linear change law. Therefore, although the output power of a single wet gas power generation material is small, the electrical output capacity can be improved through series and parallel integration, so that it can be applied to more scenarios.

[0071] like Fig. 9 As shown, the ionic hydrogel-based wet gas power generation material unit of the present invention can be integrated into a 3×6 matrix structure, thereby achieving an increase in output voltage and output power. In order to achieve stable electrical contact between the electrode and the wet gas power generation material, copper foil can be pasted to the electrode surface of the wet gas power generation material. Then, the electrodes of multiple wet gas power generation material units are interconnected through copper foil bridging. During this process, special attention should be paid to the positive and negative polarities of the electrodes to avoid reverse connection. In addition, the configuration of the integrated array can be optimized according to specific power requirements and size constraints to adapt to a variety of application scenarios and performance standards. In seasons with higher humidity, the power generation efficiency is higher, and it can provide certain power support for some local small electrical equipment (such as lighting equipment, small communication equipment, etc.).

[0072] like Fig.10 As shown, the present invention proposes an embodiment application based on ion hydrogel-based wet gas power generation materials, that is, a circuit schematic diagram of a passive energy supply device is constructed. In this embodiment, a plurality of ion hydrogel-based wet gas power generation material units 4 are integrated in series and parallel to form a wet gas power generation device 5, which acts as a power source in the circuit. The wet gas power generation device 5 is first connected in parallel with a capacitor 6, and the main function of the capacitor 6 is to store the electric energy generated by the wet gas power generation device 5. When the environment is particularly dry or harsh, the capacitor can continue to power the circuit. The capacitor 6 can supply power to the load 7, and the load can be any device that requires electrical energy, such as a sensor, a wireless transmitter, etc., thereby constructing a passive circuit system. This circuit design not only helps to reduce environmental pollution, but also can provide a continuous and stable energy supply for power facilities in remote areas, reducing operation and maintenance costs.

[0073] The above is a preferred embodiment of the present invention and is not intended to limit other forms of the present invention. A person skilled in the art may make appropriate changes or modifications based on the above technical content and apply them to other fields to form equivalent embodiments of equivalent changes. However, any simple modification, equivalent change or modification that does not deviate from the content of the technical solution of the present invention is within the protection scope of the technical solution of the present invention.

Claims

1. A novel ionic hydrogel-based moisture power generation material, characterized in that: The invention comprises a patch metal electrode (1), an ionic hydrogel (2) and a carbon-coated fabric (3); the ionic hydrogel (2) is evenly coated on one side of the carbon-coated fabric (3) to form the moisture absorption end of the moisture power generation material; the other side of the carbon-coated fabric (3) is not treated to serve as the dry end of the moisture power generation material; the patch metal electrode (1) is tightly attached to the moisture absorption end and the dry end of the ionic hydrogel (2)-based moisture power generation material, respectively, so as to construct a moisture power generation material structure with the patch metal electrode (1)-the moisture absorption end of the ionic hydrogel (2)-based moisture power generation material-the dry end of the ionic hydrogel (2)-based moisture power generation material-the patch metal electrode (1) as the basic unit; The ionic hydrogel (2) uses nano carbon black as a conductive filler and introduces hygroscopic sea salt to enhance the electrical output performance of the moisture power generation material; the dry and wet contact interface between the ionic hydrogel (2) and the carbon-coated fabric (3) is designed to be in a serrated shape.

2. A novel ionic hydrogel-based moisture power generation material as claimed in claim 1, characterized in that: The ionic hydrogel-based moisture power generation material can spontaneously absorb moisture in the environment for power generation. When the relative humidity of the environment exceeds 30%, it can effectively start working and continuously generate an open circuit voltage of 0.65V and a current of 3.2×10 -2 mA·cm -2 The short circuit current density output.

3. A novel ionic hydrogel-based moisture power generation material as claimed in claim 1 or 2, characterized in that: The plurality of ionic hydrogel-based wet gas power generation materials can be combined in series and in parallel to amplify their output voltage and output power, thereby preparing wet gas power generation devices suitable for different scenarios.

4. The use of a novel ionic hydrogel-based moisture power generation material according to claim 3, characterized in that: The moisture power generation device is used as a passive energy supply device and is suitable for self-powered sensors and wearable electronic devices.

5. A method for preparing a novel hydrogel-based moisture power generation material, characterized in that: The following steps are involved: The first step is to prepare a carbon-coated fabric (3); In the first step, the specific process of preparing the carbon-coated fabric (3) is as follows: 1.1 Cutting the textile to obtain the textile to be loaded; 1.2 Mix nano superconductive carbon black and sodium dodecylbenzene sulfonate in a certain mass ratio, and then disperse the mixture evenly in deionized water by ultrasonic dispersion to obtain a carbon black suspension; 1.3 The carbon black suspension obtained in step 1.2 is evenly coated on the textile; 1.4 drying and heat treating the textile coated with the carbon black suspension; Step 2: preparing ionic hydrogel (2); In the second step, the specific process of preparing the ionic hydrogel (2) is as follows: 2.1 Take a certain amount of hygroscopic sea salt and dissolve it in deionized water to obtain a salt solution; 2.2 Pour polyvinyl alcohol (PVA) powder into deionized water and stir rapidly for a certain period of time to obtain a PVA solution; 2.3 Slowly pour the mixed salt solution obtained in step 2.1 into the PVA solution obtained in step 2.2 and stir rapidly, and let it stand for a period of time to obtain ionic hydrogel (2); Step 3: evenly coating the ionic hydrogel (2) on one side of the carbon-coated fabric (3) to construct the moisture-absorbing end of the ionic hydrogel-based moisture power generation material; the other side of the carbon-coated fabric (3) is not treated to serve as the drying end of the ionic hydrogel-based moisture power generation material; and then placing it in a constant temperature box for a period of drying; Step 4: Using a pressure-assisted method, the patch metal electrode (1) is closely attached to the hygroscopic end and the dry end of the ion hydrogel-based moisture power generation material in a patch manner, and finally the moisture power generation material is successfully prepared.

6. The method for preparing a novel hydrogel-based moisture power generation material according to claim 5, characterized in that: In the third step, when the ionic hydrogel (2) is coated on the carbon-coated fabric (3), the dry-wet interface in the middle is designed to be serrated, and then it is placed in a constant temperature box for a period of drying.

7. The method for preparing a novel hydrogel-based moisture power generation material according to claim 5, characterized in that: The patch metal electrode (1) is gold, silver, copper, platinum or aluminum.

Citation Information

Cited By

  • High-current moisture generator under low humidity and preparation method thereof

    CN120613944A

  • Preparation method of dry-wet asymmetric moisture absorption structure and environment moisture trapping self-generating system based on dry-wet asymmetric moisture absorption structure

    CN120896472A

  • All-weather stretchable ionic liquid gel-based moisture power generation device and preparation method thereof

    CN121530224A

  • Silk-screen printing textile-based wet power generation device and preparation method and application thereof

    CN122026745A